PROMOSI MEDIA FILM BERBAHASA BENGKULU BERPENGARUH TERHADAP PENGETAHUAN DAN MOTIVASI WANITA DALAM DETEKSI DINI KANKER SERVIKS MELALUI IVA TES - Lusi Andriani; Sri Yanniarti; Desi Widiyanti; Elvi Destariyani (Politeknik Kesehatan Kementerian Kesehatan Banten, 2019)
The incidence of Cervical cancer about 16/ 100,000 women, 70% of deaths occur in poor and developing countries. It is estimated that approximately 528,000 new cases of cervical cancer and caused 266,000 people to die. The purpose of this study to determine the impact of local language movies on knowledge and motivation Women in the implementation of early detection of cervical cancer by the IVA test. This study uses a quantitative method with a design quasi-experimental pre and post-test with control group design, data were collected using a questionnaire. Samples were 60 women in the Kampung Melayu district area consists of 30 people as the intervention group and 30 in the comparison group. The data analysis used univariate, the bivariate test of T-dependent and T-test Independent, multivariate use MANCOVA. Results showed knowledge before and after intervention increased from 10.73 into 12.80 with p-value(0.000) and Motivation scores increase of 56.57 into 60.40 with p-value (0.002). There are significant differences between the intervention group and the comparison group with p-value(0.002) for the knowledge and p (0.000) for motivation. There was a significant effect of the variable Independent Movie towards Knowledge and Motivation women with pValue 0.00, covariate variable does not affect the knowledge and motivation with p-Value greater than α =0.05. Need to campaign on an ongoing basis to be able to motivate women in carrying out the examination IVA and the media that is used needs to be varied so that women interested and more easily understand the message.